Electrochemical synthesis of Pt nanoparticles on gas diffusion layers as cathodes for PEM electrolyzers. (2020) - Valero-Gómez, A.; Molina, J.; Bosch, F.
Abstract: Platinum nanoparticles have been synthesized on gas diffusion layers (GDLs) by means of electrochemical synthesis. Two types of GDLs were used (hydrophobic and hydrophilic) to study the effect of surface properties on the electrodeposition of Pt nanoparticles. Better coverage of Pt nanoparticles has been observed in the case of using a hydrophilic carbon GDL; nanoparticles with lower size were synthesized as well. Characterization of hydrogen evolution reaction by cyclic voltammetry showed a better performance of the electrodes synthesized by electrochemical methods when compared with commercial ones with an equal Pt loading (2 mg·cm -2 )